Comparison of Differences in Chemical Composition and Related Antioxidant Activity of Snow Lotus from Different Origins. Issue 1 (30th December 2022) - Zhang, Huirong; Li, Xuan; Meng, Xianyao; Ling, Xiao; Li, Shuowen; Song, Guanjie; Li, Li
Abstract: The snow lotus is an endangered traditional Chinese medicinal herb. Saussurea involucrata, Saussurea laniceps, and Saussurea medusa, the three main snow lotus species (five herbs and two S. involucrata cell cultures), were selected for this study. Snow lotus (XLs) was extracted using 75 % (v/v) ethanol. Two reversed phase‐high performance liquid chromatography‐diode array detector methods were developed and validated for the determination of 10 representative components in XLs. The antioxidant efficacy of XLs and their components was investigated using DPPH, ABTS free radical scavenging, and ROS inhibition experiments. The results showed that the IC50 for DPPH scavenging ranged from 0.06–0.29 mg/mL for XLs and from 0.13–0.63 mg/mL for ABTS, and could downregulate ROS to varying degrees. The results of the antioxidant activity showed that rutin, quercetin, and isochlorogenic acid A contributed to the antioxidant capacity of XLs. The high content and activity of the cell cultures indicate that they can serve as an effective alternative to snow lotus, thus providing a theoretical basis for the selection of herbs and cell cultures to fulfil various needs. Abstract :